2019
DOI: 10.3390/ijerph16040666
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quality of Life and Work Ability of Taxi and Motorcycle Taxi Drivers: Evidence from Brazil

Abstract: Urban transport drivers, specifically taxi and motorcycle taxi drivers, are exposed to particular environmental, societal, and health situations related to their occupation. To compare work capacity and quality of life of taxi and motorcycle taxi drivers, and correlate quality of life and work ability, a cross-sectional descriptive study was conducted among 232 motorcycle taxi drivers and 60 male taxi drivers in urban cities of Brazil. Three instruments were used for evaluation: a questionnaire on sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
6
0
3
Order By: Relevance
“…Finally, a randomized controlled trial of bus drivers reported that work ability and vitality decreased significantly in both groups as the high season progressed and work-related fatigue and psychosomatic health complaints increased 32 . As compared with motorcycle taxi drivers, taxi drivers have better self-perception of their WA and both subgroups show a positive relationship between quality of life and WAI 16 . However, most evidence comes from cross-sectional studies, precluding any causal relationship to be established on these associations.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Finally, a randomized controlled trial of bus drivers reported that work ability and vitality decreased significantly in both groups as the high season progressed and work-related fatigue and psychosomatic health complaints increased 32 . As compared with motorcycle taxi drivers, taxi drivers have better self-perception of their WA and both subgroups show a positive relationship between quality of life and WAI 16 . However, most evidence comes from cross-sectional studies, precluding any causal relationship to be established on these associations.…”
Section: Discussionmentioning
confidence: 98%
“…32 As compared with motorcycle taxi drivers, taxi drivers have better self-perception of their WA and both subgroups show a positive relationship between quality of life and WAI. 16 However, most evidence comes from cross-sectional studies, precluding any causal relationship to be established on these associations. We suggest longitudinal studies on this topic, focusing on WA, work-related quality of life, and general health.…”
Section: Lifestyle and Work Activities Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…En cuanto a un lugar para descansar durante un día de trabajo, la mayor parte de ellos, no tenían un lugar para tener un período de ocio y descanso. También se evidencia que los conductores de motocicletas eran más jóvenes, trabajaban menos horas por día y experimentaban más accidentes laborales que los conductores de taxis 37 .…”
Section: Calidad De Vidaunclassified
“…Respecto a la calidad de vida, la evidencia señala, que la calidad de vida, se relaciona con distintos ámbitos de una persona, como lo es el trabajo, salud, vida familiar, evaluándose como un conjunto de aspectos, que pueden evaluarse de forma objetiva o subjetiva que interactúan entre sí con el medio, y no como una característica meramente idiosincrática de cada persona. Los artículos abordados señalan que la calidad de vida en estos trabajadores se ve afectada por distintos aspectos, como trabajo, condiciones laborales, salud, situación económica, las cuales interfieren de forma negativa en la vida de una persona 36,37,38 .…”
Section: E-issn: 2346-3414unclassified